Synthesis of Zeolite A From Coal Fly Ash with Variation of Si/Al Molar Ratio - Andarini, Novita; Haryati, Tanti; Lutfia, Zuhrotul (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2018)
Fly ash containing 30-36% silica and 14,52-23,78% alumina can be potentially as raw material for synthetic zeolite such as zeolite A. Zeolite A is an aluminosilicate mineral which is rich in alumina so that this zeolite has a good cation exchange capability. Zeolite A has been synthesized by hydrothermal treatment after NaOH fusion. Fly ash has been fused with NaOH at 550 0C for 40 minutes and hydrothermally treated at 1000C for 5 hours. The hydrothermal treatment was conducted in some various Si/Al molar ratios from 0.90; 1.00.; 1.05; to 1.24. The zeolite A was then analyzed using XRD and XRF. The best zeolite A based on XRD result is zeolite with Si/Al molar ratio of 1.1 with crystallinity of 96,80%. The x-ray fluorescence result showed that the Si/Al molar ratios of the four zeolite samples were close to of Si/Al molar ratios of 1, 1.1, 1.21.3 respectively.Keywords: Fly ash, Zeolite A, Hydrothermal Fusion